Memahami Ekonomi dan Keuangan Islam - Cinta Rahmi (Jurnal Riset Ekonomi dan Akuntansi, 2023)
The Islamic financial economy is progressing in both developing and developed countries. The financial industry and other forms of Islamic economic institutions are growing, ranging from the Middle East, Asian region, to Western countries such as the UK. Unfortunately, the development of Islamic economics at the practical level has not been matched by the development of Islamic economics on the theory side. Whereas as a science, Islamic economics also not only needs to be transformed into a practical-implementative level, but must also be accompanied by developments on the academic-theoretical side. The gap between the availability of limited resources and unlimited human needs is an important issue that must be addressed by the concept of Islamic-based economics, where the goal of the Islamic economic system is the benefit of each individual. The research method used in this research is the library research method. By reviewing previous journals that are relevant to studies related to economics and Islamic finance. The results of this study indicate that Islamic finance is a manifestation of economic behavior based on Islamic teachings which includes how to view economic problems, analyze, and propose alternative solutions to various economic problems. The emphasis of Islamic economics is on how Islam provides views and solutions to various economic problems faced by humanity in general.